2018
DOI: 10.1039/c8nr00719e
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the nature of low-temperature photoluminescence peaks by laser treatment in van der Waals epitaxially grown WS2 monolayers

Abstract: Monolayers of transition metal dichalcogenides (TMD) are promising materials for optoelectronics devices. However, one of the challenges is to fabricate large-scale growth of high quality TMD monolayers with the desired properties in order to expand their use in potential applications. Here, we demonstrate large-scale tungsten disulfide (WS) monolayers grown by van der Waals Epitaxy (VdWE). We show that, in addition to the large structural uniformity and homogeneity of these samples, their optical properties a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…This effect is rather interesting, suggesting that X normalD band can be sensitive also to other forms of radiation, being useful for some applications. Similar effects have been observed also by other groups …”
supporting
confidence: 92%
See 1 more Smart Citation
“…This effect is rather interesting, suggesting that X normalD band can be sensitive also to other forms of radiation, being useful for some applications. Similar effects have been observed also by other groups …”
supporting
confidence: 92%
“…In addition to the charge‐neutral A 0 exciton peak, a charged trion A peak is also often found at about 43 meV lower energies . At low temperatures ( T ≈ 10 K), a broad defect‐bound exciton band ( X normalD ) with a peak position of about 1.9 eV has been found to dominate the PL spectra . This spectral region includes also a single‐photon emission (a series of sharp peaks in the defect band region) that has been detected in the low‐temperature PL spectra of WS 2 monolayers and in other 2D compounds .…”
mentioning
confidence: 93%
“…It can be shown that the parameter carries a spatial dependence in addition to the macroscopic time-dependence, by applying spatial statistics on PL maps that accounts for the spatial inhomogeneity. In this measurement, a separate monolayer flake is chosen and the laser power is increased to , from in the previous measurement, which is expected to increase the rate of change of the spectral weightings 44 , 51 . Rapid spectral tuning is crucial for scalability as this will reduce the overall treatment time of large-area flakes.…”
Section: Resultsmentioning
confidence: 99%
“…The intensities of the Raman peaks were also converted to absolute scattering probability using the Si peak intensity as a reference 28 with corrections for Fabry-Perot effects modelled using the reflectivity spectra as were performed in our previous paper 8 . The laser power incident on the sample was kept below 100 µW to avoid photo-doping and laser heating effects 45,46 .…”
Section: Methodsmentioning
confidence: 99%